The far right today - Mudde, Cas 1967- (Polity, 2019)
The Far Right TodayCas MuddeThe far right is back with a vengeance. After several decades at the political margins, far-right politics has again taken center stage. Three of the world’s largest democracies - Brazil, India, and the United States - now have a radical right leader, while far-right parties continue to increase their profile and support within Europe.In this timely book, leading global expert on political extremism Cas Mudde provides a concise overview of the fourth wave of postwar far-right politics, exploring its history, ideology, organization, causes, and consequences, as well as the responses available to civil society, party, and state actors to challenge its ideas and influence. What defines this current far-right renaissance, Mudde argues, is its mainstreaming and normalization within the contemporary political landscape. Challenging orthodox thinking on the relationship between conventional and far-right politics, Mudde offers a complex and insightful picture of one of the key political challenges of our time.